The necessity of change – how the fourth industrial revolution urges the entrepreneurs to alter their leadership attributes - Ronnen Avny (President University, 2022)
Innovation leadership is critical in enhancing a firm’s success in today’s changing markets. This research investigates the changes in entrepreneurial leadership attributes amid the fourth industrial revolution and the fast pace of technological advancement. This research tackles a gap in the current knowledge and reveals interesting outcomes covering the barely researched sub-domain of the fourth industrial revolution and examine how the entrepreneurial leadership should be adjusted for better coping with the current fast-paced technology environment, and how the entrepreneur should adjust the leadership attributes in order to fully exploit the advantages of this revolution and gain a competitive advantage. The content analysis method used for this research utilized written data regarding 23 leaders from 20 companies from the latest 19th century during the first industrial revolution until the current fourth industrial revolution. Results reveal noticeable leadership attributes emphasized in the fourth industrial revolution, such as communication, coaching, innovation, forecasting future, team-builder, and more. Those attributes are in tight correlation with the current novel digital leadership paradigm and the known effects of the fourth industrial revolution on the firms and leaders. Results reveal that current entrepreneurs tend to be open-minded while avoiding rejecting innovation from other firms and are willing to share the experience with the adjacent technology ecosystem.